KEGIATAN BERKEBUN MELALUI SENTRA ALAM SEBAGAI PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENGEMBANGKAN KOGNITIF ANAK USIA DINI DI TK KASIH IBU KERTEK - Risma Sofiyana; ahmad khoiri; nur farida (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
AbstractThe research aims to improve early childhood cognitive development through the media of gardening activities through a local wisdom-based nature center at Kasih Ibu Kertek Kindergarten, Wonosobo. Knowing learning gardening activities from preparing planting media to how to care for plants. The type of research used is field qualitative research. The research subjects were group B students in Kindergarten Ibu Kartek Wonosobo. Methods of data collection carried out by researchers using: Observation, Interview and Documentation. The results showed: (1) Learning gardening activities can improve cognitive skills in Kindergarten Kasih Ibu Kertek by 12.6%. (2) The benefits of gardening activities are that children are able to know the types of plants, children are able to observe the process of plant growth from seeds to the growth of leaves, children are able to apply gardening activities. (3) The supporting factor for gardening activities is the presence of empty land in the school yard so that it can be used for learning, while the inhibiting factor is that children are afraid of getting dirty, complain easily and get tired easily when outside because they are exposed to direct sun but many children also passion when learning gardening. The conclusion of this study is that gardening activities through nature centers as local wisdom-based learning can improve the cognitive development of early childhood in the Kindergarten of Kasih Ibu Kertek Wonosobo. Keywords: Learning gardening, Aspects of Child Development